The Role of Volition in Graduate Students’ Academic Writing - Krismalita Sekar Diasti; Concilianus Laos Mbato (Tell : Teaching of English Language and Literature Journal, 2023)
Due to Covid-19 outbreak, students and teachers experience a rapid shift from conventional to online learning which requires students to be more self-regulated learners. The purpose of this study is to discover how graduate students remain focused and keep devoting effort in academic writing task completion. This research employed a qualitative study involving 13 graduate students of the English Education Master Program of a private university in Indonesia. Data were collected by distributing questionnaire and conducting interview. The data obtained from the questionnaire were analysed using descriptive statistics. Further, open coding techniques were utilized to examine the interview data. There are three major findings drawn in this study, namely, volitional strategies used by students in the academic writing task, persistence amid pandemic situation, and the role of volition in maintaining students’ motivation. The themes describe how students show their determination during the goal-achievement process of academic writing assignments. Students frequently encounter hardships in their learning process which might distance themselves from accomplishing the learning demands. This study shed the light on fruitful merits of volition, particularly in driving students to stay focused despite challenges or distracting situation.